The Principle of Convenience in Islamic Sharia: An Analysis of the Rules of Al-Masyaqqah Tajlibut Taysir - Aga Setiawan; Sonya Noprisa Sumantri (ISNU Sumatera Utara, 2025)
Leniency (rukhsah) in carrying out Islamic sharia is a form of convenience given by Allah SWT to His people, as enshrined in the rules of fiqh